2015
DOI: 10.1016/j.pdpdt.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between photodynamic and antibiotic therapies for treatment of footpad dermatitis (bumblefoot) in Magellanic penguins (Spheniscus magellanicus)

Abstract: The findings of this study attest to the effectiveness of photodynamic therapy for the treatment of stage III bumblefoot in Spheniscus magellanicus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The use of PDT in veterinary medicine is still being investigated, studies have shown promising results using the technique in the treatment of different diseases [59][60][61][62]. We believe that further investigations need to be carried out and that they must extrapolate the in vitro assays.…”
Section: Regardlessmentioning
confidence: 99%
“…The use of PDT in veterinary medicine is still being investigated, studies have shown promising results using the technique in the treatment of different diseases [59][60][61][62]. We believe that further investigations need to be carried out and that they must extrapolate the in vitro assays.…”
Section: Regardlessmentioning
confidence: 99%
“…The application of APDT in veterinary medicine is still under investigation, with satisfactory results in dermatological diseases [6]. We hope that these clinical results will encourage colleagues and researchers in the development of subsequent studies to establish clinical protocols.…”
Section: Discussionmentioning
confidence: 91%
“…In the penguins at Santos Municipal Aquarium, we hypothesize that the rough artificial scenography of the exhibit may be the main causal factor for bumblefoot. In order to prevent the occurrence of bumblefoot by reducing inactivity, plenty of space was provided for the penguins to swim in the exhibit pools and through the underwater gateways that connect three sections of the Pinguin ario (Sellera et al, 2014;Nascimento et al, 2015). Studies carried out elsewhere showed that enhancing the time birds spent in the water by using environmental enrichment resulted in a significant reduction or complete remission of bumblefoot lesions in captive Magellanic penguins (Reisfeld et al, 2013).…”
Section: Discussionmentioning
confidence: 99%